Kualitas Spermatozoa Kambing Peranakan Boer yang Dipreservasi dengan Pengencer Air Kelapa Muda dan Ekstrak Daun Kelor - Muhammad Rizal (Jurnal Ilmu dan Industri Peternakan, 2022)
ABSTRACT Moringa leaves contain various nutrients that can protect spermatozoa during semen preservation. The purpose of this study was to examine the ability of moringa leaf extract with different concentrations of coconut water extender on the quality of Boer crossbreed goat spermatozoa preserved at 3-5°C. The treatment of this study was the concentration level of moringa leaf extract in coconut water extender. Fresh semen was divided into five tubes and diluted with 80% coconut water + 20% egg yolk (P0, control), 79% coconut water + 20% egg yolk + 1% moringa leaf extract (P1), 77% coconut water + 20% egg yolk + 3% moringa leaves ectract (P2), 75% coconut water + 20% egg yolk + 5% moringa leaf extract (P3), and 73% coconut water + 20% egg yolk + 7% moringa leaf extract (P4), respectively. The variables observed were motility and spermatozoa viability. Results of this study showed that supplementation of different concentrations of moringa leaf extracts in coconut water extender was significantly (P<0.05) on motility and viability of Boer crossbreed goat spermatozoa during preservation. Supplementation of 3% moringa leaf extract in coconut water extender was better than 1, 5, and 7% in maintain the quality of Boer crossbreed goat spermatozoa during preservation. Keywords: Moringa Leaf Extract, Semen Preservation, Boer Crossbreed Goat